FAKTOR YANG BERHUBUNGAN DENGAN MINAT MASYARAKAT DALAM KEIKUTSERTAAN BPJS KESEHATAN DI KECAMATAN KUNTO DARUSSALAM KABUPATEN ROKAN HULU - Seprina, Zurni; Fitria, Eliza; Rulen, Betty Nia; Ningsih, Yuni Warna (Ensiklopedia of Journal, 2025)
Universal Health Coverage (UHC) is a global health development concept that ensures that everyone has access to fair, comprehensive and quality health services without financial barriers. In Indonesia, UHC is realized through the National Health Insurance Program-Healthy Indonesia Card (BPJS-KIS). The lowest UHC achievement in Rokan Hulu Regency is Kunto Darussalam sub-district in 2023 out of 8,414 residents, only 4,640 people are registered as BPJS Health participants. The purpose of the study was to determine the factors associated with Community Interest in BPJS Health Participation in Kunto Darussalam District, Rokan Hulu Regency. This type of research is quantitative observational analytic with the type of Analytical Cross Sectional Study design (Cross Sectional Study). The population is all people who live in Kunto Darussalam District in 2024 which amounted to 8.414 people with a sample size of 100 people selected using the Simple Random Sampling technique. Data were analyzed univariately and bivariately using Chi Square statistical test. The results showed that there was a relationship between knowledge (P value: 0.020), income (P value: 0.017), family supORt (P value: 0.046) and there was no relationship between attitude (P value: 0.723), gender (P value: 0.883) with Community Interest in BPJS Health Participation in Kunto Darussalam District, Rokan Hulu Regency. It is recommended to the community who are respondents to be able to increase their knowledge about BPJS services, be able to sort out the correct information about BPJS and BPJS Health Rokan Hulu district to socialize the registration mechanism and benefits of BPJS Health to all levels of societyKeywords: BPJS Health, Family SupORt, Knowledge, Income